The emergence of the modern Abrahamic cause and the motives for its establishment - Sajet, Haider; Tohme, Abdul Karim (Al-Adab Journal, 2024)
The research sheds light on the modern Abrahamic claims that have emerged in recent years, according to which human brotherhood was considered a comprehensive slogan for religions that all trace back to one origin, which is the Prophet Abraham (peace be upon him). As a result, more than one Arab Islamic country signed agreements with the usurping Zionist entity under the supervision of The United States of America titled (Abraham Accords) under the pretext of peace and brotherhood and other similar titles, through which it is intended to export these concepts by turning them around and making them socially acceptable terms. The research proves that these false claims are not new, but rather have roots and credibility, ancient and modern, and the main goal is to know the implications of that claim and confront it consciously. And knowledge so that the ravages of time do not attack the emerging generation of this generation, especially the youth, and so that everything is put in its place in the light of wisdom and correct standards established in the verses of the Holy Qur’an and the hadiths of the Prophet, his family, and the chosen companions.